Copper plating additive composition, copper plating solution and use thereof

By using specific copper coating additives and improved copper coating liquid in copper brush coating technology, the problems of uneven copper layer and easy perforation of plastic film are solved, and the uniformity and thickness of the copper layer are improved, meeting the needs of high brightness and low resistance.

JP2025510238AActive Publication Date: 2025-04-14JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024556682
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2023-03-23
Publication Date
2025-04-14
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

The existing copper brush coating technology has problems such as uneven copper layer, inconspicuous surface, easy perforation of plastic film and failure to meet electrical properties, especially in improving the thickness and uniformity of the copper layer.

Method used

The copper coating additives containing 1,4-cyclohexene glycol monoethyl ether glycolic acid, potassium phenylphenyl pyruvate and ammonia polyol compounds are used to combine copper sulfate and chloride ions to improve the uniformity and thickness of the copper layer through an improved copper brush coating method.

Benefits of technology

It significantly improves the uniformity and thickness of the copper layer, improves the brightness and color saturation of the copper layer, avoids the perforation problem of plastic film, and meets the requirements of low resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510238000001_ABST
    Figure 2025510238000001_ABST
Patent Text Reader

Abstract

The present application relates to a copper plating additive composition, a copper plating solution, and a copper brush plating method using the same. The copper plating additive composition includes 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and an aminopolyol compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-references to related applications This application claims priority to and the benefit of Chinese patent applications filed on March 25, 2022, with application numbers 2022102992129 and 2022102993386, and international applications filed on May 24, 2022, with application numbers PCT / CN2022 / 094709 and PCT / CN2022 / 094681, the entire contents of which are incorporated by reference.

[0002] The present application relates to the technical field of copper plating, and in particular to a copper plating additive composition, a copper plating solution and uses thereof. [Background technology]

[0003] Electric brush plating, also known as metal brush plating, quick plating or brush plating, is an electrochemical process in which a plating brush immersed in a plating solution serves as the anode, and metal ions are discharged and crystallized on the surface of the cathode (workpiece) to form a metal coating layer.

[0004] Copper brush plating is mainly used in fields with high requirements for conductivity, such as electronics, electricity, and aerospace, and has extremely high practical value, especially in partial plating and plating layer repair. During the operation process, the relative movement speed between the cathode and the anode is fast, so a high current density (several to several tens of times higher than the current density used in the plating bath) can be used. In addition, the plating speed is extremely fast (5 to 10 times faster than bath plating) due to the high copper ion content in the plating solution of copper brush plating. In recent decades, scientists from all over the world have conducted in-depth and long-term research on cyanide-free copper plating process, and cyanide-free copper plating technology has now realized industrialized production and achieved good social and economic benefits, but cyanide-free copper brush plating still has defects such as uneven plating layer and dull appearance of the plating layer.

[0005] In addition, in the prior art, two processes, namely magnetron sputtering + electroplating or deposition + electroplating, are usually used to perform double-sided copper plating on the surface of a plastic film (e.g., polypropylene PP or polyethylene terephthalate PET) with a thickness of 3.2 μm to 12 μm. These two processing processes have the problem that the quality of the processing between steps is not high. The main difficulties are that the thickness of the copper film formed after magnetron sputtering or deposition is uneven, and burn holes are easily generated during copper electroplating, and failures such as film perforation and film cracking occur frequently, resulting in an extremely low yield rate.

[0006] In addition, the thickness of the copper film produced by magnetron sputtering or deposition is not enough, so the sheet resistance is too high, usually about 2000 mΩ. Therefore, it is necessary to increase the thickness of the copper layer to reduce the sheet resistance to less than 500 mΩ. The traditional solution is to adopt acid copper electroplating, which can obtain a copper plating layer with dense crystals and achieve the required sheet resistance. However, the biggest difficulty at present is that the cathode roller contacting the plastic film during the acid copper electroplating process is plated with copper, and the copper-plated part of the cathode roller is easy to break through the plastic film layer, causing holes in the plated plastic film and resulting in failure. At the same time, the thickness uniformity of the plating layer may be poor, the edge of the film is easy to burn, and failures such as burn holes, perforations, and film cracks in the film layer occur, and finally the yield rate and efficiency of the plated film are both low. On the other hand, if the sheet resistance is significantly reduced in the magnetron sputtering or deposition process, the risk of perforations and burn holes in the film is greatly increased. Furthermore, the later acid copper electroplating process cannot adopt high electroplating current, which greatly reduces the thickness of the film layer and also makes it impossible for the sheet resistance to fall within the required range of the finished product. On the contrary, the current of acid copper electroplating is too high, which also increases the possibility and degree of the cathode roller being copper plated, and the film surface of the plastic film may be pierced or burned at any time. This makes it clear that the magnetron sputtering + acid copper electroplating or evaporation + acid copper electroplating process is complicated to operate and difficult to adjust and control, not to mention the control of the yield rate of the finished product in one processing run.

[0007] In addition, according to a summary of the phenomena occurring in the laboratory and factory production, the metallized plastic film becomes brittle after undergoing the acid copper electroplating process, and acid copper electroplating cannot be repeated multiple times. After undergoing one electroplating (maximum two), the film will easily crack when pulled, resulting in the product being rejected. In addition, all the product films processed in the previous process will be discarded, which is too wasteful and has no economic value.

[0008] To summarize the above, the current electric brush plating has defects such as uneven plating layer and not bright enough appearance of plating layer, and there are many more problems in the copper brush plating process of plastic film that are difficult to coordinate. The industry urgently needs a copper plating solution that can significantly improve the uniformity, brightness and color saturation of the plating layer with a fast plating speed, and a copper brush plating process of plastic film that can improve the thickness and uniformity of the copper layer, prevent the plastic film from being pierced, ensure the sheet resistance of the finished film meets the standard, and have good bonding force between the copper plating layers. Summary of the Invention [Problem to be solved by the invention]

[0009] According to embodiments of the present application, the present application provides a copper plating additive composition, a copper plating solution, and a copper brush plating method. [Means for solving the problem]

[0010] The technical proposal is as follows:

[0011] A copper plating additive composition comprising 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide and an aminopolyol compound.

[0012] In one embodiment, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and the aminopolyol compound is (0.6-1.0):(1.2-2.0):(1.8-3.0).

[0013] In one embodiment, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and the amino polyol compound is (0.8-1.0):(1.5-2.0):(2.0-3.0).

[0014] In one embodiment, the amino polyol compound is 3-amino-1,2-propanediol.

[0015] The present application further provides a copper plating solution comprising the above copper plating additive composition.

[0016] In one embodiment, the copper plating solution further comprises water, copper sulfate (CuSO4), sulfuric acid, and chloride ions. The chloride ions can be derived from a chloride ion-containing compound that is soluble in water, such as hydrogen chloride.

[0017] In one embodiment, the copper plating solution per liter contains water, 1,4-Cyclohexanedione monoethylene acetal 0.06g~0.10g, Potassium phthalimide 0.12g to 0.20g, Aminopolyol compound 0.18g to 0.30g, Copper sulfate 120g~220g, 50g-70g sulfuric acid, and Contains 60mg to 80mg of chloride ions.

[0018] In one embodiment, the copper plating solution further comprises a brightener, a surfactant and a leveling agent.

[0019] In one embodiment, the brightener is one or more selected from ethylene thiourea, benzimidazole, and fatty amine ethoxy sulfonate.

[0020] In one embodiment, the surfactant is one or two selected from sodium dodecylsulfonate and 3,3'-dithiobis(sodium 1-propanesulfonate).

[0021] In one embodiment, the leveling agent is one or more selected from polyethylene glycol, 1,4-butyne diol, and polyethyleneimine alkyl salt.

[0022] In one embodiment, the copper plating solution per liter contains water, 1,4-Cyclohexanedione monoethylene acetal 0.06g~0.10g, Potassium phthalimide 0.12g to 0.20g, Aminopolyol compound 0.18g to 0.30g, Copper sulfate 120g~220g, Sulfuric acid 50g-70g, Chloride ion 60mg~80mg, Polishing agent 0.0002mg~0.0008mg, Surfactant 0.05mg to 0.1mg, and Contains 0.05g to 0.1g of leveling agent.

[0023] In one embodiment, the copper plating solution per liter contains water, 1,4-Cyclohexanedione monoethylene acetal 0.06g~0.10g, Potassium phthalimide 0.12g to 0.20g, Aminopolyol compound 0.18g to 0.30g, Copper sulfate 120g~220g, Sulfuric acid 50g-70g, Chloride ion 60mg~80mg, Ethylenethiourea 0.0002mg~0.0008mg, Sodium dodecyl sulfonate 0.05mg to 0.1mg, and Contains 0.05g to 0.1g of polyethylene glycol.

[0024] The present application further provides a method for copper plating a surface of a substrate, comprising the step of contacting the substrate with the copper plating solution to perform a copper plating process.

[0025] In one embodiment, the copper plating method for the surface of the substrate is a copper brush plating method.

[0026] In one embodiment, the method for copper plating the surface of the substrate is performed by one or more parameters selected from the following: plating temperature 35°C to 45°C, plating time 1 min to 2 min, and operating voltage 2V to 7V.

[0027] In some embodiments, the method for copper plating the surface of the substrate is performed under the following parameters: plating temperature 35°C to 45°C, plating time 1min to 2min, and operating voltage 2V to 7V.

[0028] The present application further discloses a copper brush plating method for providing a coating layer on a surface of a substrate, the method comprising: performing a copper plating process on a surface of a substrate using a copper brush plating method to form a copper film on the surface of the substrate, the anode during the copper plating process being a brush plating roller, and the copper plating process further comprising contacting the surface of the substrate with a copper plating solution.

[0029] In one embodiment, the copper brush plating is performed at one or more parameters selected from the following: plating temperature: 0°C to 45°C; plating time: 1 min to 10 min; operating voltage: 1 V to 7 V; and relative movement speed of the plastic film to the brush plating roller: 3 m / min to 10 m / min.

[0030] In some embodiments, copper brush plating is performed under the following parameters: plating temperature 0°C to 45°C, plating time 1min to 10min, operating voltage 1V to 7V, relative movement speed of the plastic film to the brush plating roller 3m / min to 10m / min.

[0031] In one embodiment, the copper brush plating method further includes the step of performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film, thereby forming a substrate.

[0032] In some embodiments, the copper plating solution used in the copper plating process includes water, copper sulfate (CuSO4), sulfuric acid, chloride ions, 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and an aminopolyol compound.

[0033] In some embodiments, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and amino polyol compound is (0.6-1.0):(1.2-2.0):(1.8-3.0).

[0034] In one embodiment, the copper brush plating method includes the steps of: performing a first copper plating process on a plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film, thereby forming a substrate; performing a second copper plating process on the first copper film using a copper brush plating method to form a third copper film on the first copper film; the anode during the second copper plating process is a brush plating roller; The second copper plating process further comprises contacting the first copper film with a copper plating solution comprising the copper plating additive composition.

[0035] In one embodiment, the copper plating solution used in the second copper plating process includes water, copper sulfate (CuSO4), sulfuric acid, chloride ions, 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and an aminopolyol compound.

[0036] In some embodiments, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and amino polyol compound is (0.6-1.0):(1.2-2.0):(1.8-3.0).

[0037] In one embodiment, a copper brush plating method includes: performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film and a second copper film on the other surface of the plastic film; performing a second copper plating process on the first copper film and the second copper film using a copper brush plating method to form a third copper film on the first copper film and a fourth copper film on the second copper film; the anode during the second copper plating process is a brush plating roller; The second copper plating process further comprises contacting the first copper film and the second copper film with a copper plating solution containing the copper plating additive composition.

[0038] In one embodiment, the copper plating solution for the second copper plating process includes water, copper sulfate (CuSO4), sulfuric acid, chloride ions, 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and an aminopolyol compound.

[0039] In some embodiments, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and amino polyol compound is (0.6-1.0):(1.2-2.0):(1.8-3.0).

[0040] In one embodiment, the plastic film is made of polypropylene (PP), polyethylene terephthalate (PET), polyethylene (PE), polyacrylonitrile (PAN), polyimide (PI) or polydimethylsiloxane (PDMS).

[0041] In one embodiment, the brush plating roller is covered with a sponge-like liquid-absorbing layer.

[0042] In one embodiment, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and aminopolyol compound used in the copper brush plating method is (0.6-1.0):(1.2-2.0):(1.8-3.0).

[0043] In one embodiment, the amino polyol compound used in the copper brush plating method is 3-amino-1,2-propanediol.

[0044] In one embodiment, the copper plating solution per liter used in the copper brush plating method comprises water, 1,4-Cyclohexanedione monoethylene acetal 0.06g~0.10g, Potassium phthalimide 0.12g to 0.20g, Polyol compound 0.18g to 0.30g, Copper sulfate 120g~220g, 50g-70g sulfuric acid, and Contains 60mg to 80mg of chloride ions.

[0045] In one embodiment, the physical vapor deposition is a magnetron sputtering or evaporation method.

[0046] In one embodiment, the first copper film and the second copper film each have a sheet resistance of 2200 mΩ or less.

[0047] In one embodiment, the first copper film and the second copper film each independently have a sheet resistance of 100 mΩ to 2200 mΩ.

[0048] In one embodiment, the first copper film and the second copper film each have a thickness independently ranging from 0.1 μm to 0.5 μm.

[0049] In one embodiment, the second copper plating process is performed under one or more parameters selected from a plating temperature of 0°C to 45°C, a plating time of 1 min to 10 min, an operating voltage of 1 V to 7 V, and a relative movement speed of the plastic film with respect to the brush plating roller of 3 m / min to 10 m / min.

[0050] In one embodiment, the second copper plating process is performed under the following parameters: plating temperature 0° C. to 45° C., plating time 1 min to 10 min, operating voltage 1 V to 7 V, and relative movement speed of the plastic film with respect to the brush plating roller 3 m / min to 10 m / min.

[0051] In one embodiment, the plastic film has a thickness of 3.2 μm to 12 μm.

[0052] In one embodiment, the copper plating solution used in the copper brush plating method further includes at least one of a brightener, a surfactant, and a leveling agent.

[0053] In one embodiment, the brightener used in the copper brush plating method is one or more selected from ethylene thiourea, benzimidazole, and aliphatic amine ethoxysulfonate.

[0054] In one embodiment, the surfactant used in the copper brush plating method is one or two selected from sodium dodecylsulfonate and 3,3'-dithiobis(sodium 1-propanesulfonate).

[0055] In one embodiment, the leveling agent used in the copper brush plating method is one or two of polyethyleneimine alkyl salt and polyethylene glycol.

[0056] In one embodiment, the copper plating solution per liter used in the copper brush plating method comprises water, 1,4-Cyclohexanedione monoethylene acetal 0.06g~0.10g, Potassium phthalimide 0.12g to 0.20g, Polyol compound 0.18g to 0.30g, Copper sulfate 150g~220g, Sulfuric acid 50g-70g, Chloride ion 60mg~80mg, Polishing agent 0.0002mg~0.0008mg, Surfactant 0.05mg to 0.1mg, and Contains 0.05g to 0.1g of leveling agent. [Brief description of the drawings]

[0057] In order to more clearly explain the embodiments of the present invention, reference will now be made to the drawings, which are for illustrative purposes only and are not intended to limit the scope of the present application.

[0058] [Figure 1] 1 is a flow chart of a copper brush plating method for providing a coating layer on a surface of a plastic film in accordance with one or more embodiments of the present application. [Diagram 2] FIG. 1 is a schematic diagram of a copper brush plating apparatus for use in a copper brush plating method in accordance with one or more embodiments of the present application. [Diagram 3] FIG. 2 is a diagram of a copper plated layer (a) in Example 1 of the present application, a diagram of a copper plated layer (b) in Example 2 of the present application, and a diagram of a copper plated layer (c) in Example 3 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0059] In order to make the object, technical solution and advantages of the present invention clearer, the present invention will be described in detail with reference to the drawings and examples. It should be understood that the specific embodiments described herein are only for illustrating the present disclosure, and are not for limiting the present disclosure.

[0060] Unless otherwise defined, all technical or scientific terms used herein have the same meaning as those skilled in the art understand. In this specification, these terms are used to describe the examples of the present disclosure and are not intended to limit the present application. As used herein, the term "and / or" refers to any and all combinations of one or more of the applicable items.

[0061] As used herein, the use of "including," "having," and "containing" is intended to cover a non-exclusive inclusion and may include additional parts unless express limiting terms such as "only," "consisting of," or the like are used.

[0062] In addition, in the description of the present application, the orientations or positional relationships indicated by directional terms such as "center," "lateral," "longitudinal," "length," "width," "thickness," "up," "down," "front," "rear," "left," "right," "up," "down," "vertical," "horizontal," "top," "bottom," "inside," "outside," "clockwise," "counterclockwise," etc. are based on the orientations or positional relationships shown in the drawings, and are intended merely to facilitate and simplify the description of the present application, and are not intended to indicate or imply that the indicated devices or elements necessarily have a specific orientation or are required to be constructed and operated in a specific orientation, and cannot be understood as limiting the specific scope of protection of the present application.

[0063] When describing positional relationships, unless otherwise noted, when an element, e.g., layer, film, or substrate, is referred to as being "on" another film layer, it may be directly on the other film layer or there may be intermediate film layers present. Further, when a layer is referred to as being "below" another layer, it may be directly below or there may be one or more intermediate layers present. Additionally, when a layer is referred to as being "between" two layers, it may be the only layer between the two layers or there may be one or more intermediate layers present.

[0064] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum value, the maximum value, and each value between the minimum and maximum values ​​of the range. Furthermore, when a range refers to an integer, it includes each integer between the minimum and maximum values ​​of the range. It should be noted that when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges contained therein.

[0065] Unless stated to the contrary, singular terms may include plurals and are not to be construed as having a number of one.

[0066] It should be noted that the drawings are not drawn to a 1:1 scale, and the relative dimensions of each element are illustratively depicted in the drawings to facilitate understanding of the present application, but are not necessarily drawn to a true scale, and the scale in the drawings is not intended to limit the present application.

[0067] The present application provides a copper plating additive composition that can significantly improve the thickness, brightness and whiteness of the plating layer.

[0068] The technical proposal is as follows:

[0069] The copper plating additive composition includes 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide and an aminopolyol compound.

[0070] Here, 1,4-cyclohexanedione monoethylene acetal can significantly improve the brightness of the copper brush plating layer. Potassium phthalimide can effectively increase the dissolution efficiency of 1,4-cyclohexanedione monoethylene acetal, refine the crystal grains, level, and improve the uniformity and thickness of the plating layer. Aminopolyol compound can greatly change the color tone of the copper layer and make it more vivid. In addition, the copper plating additive composition has the advantages of being environmentally friendly, non-toxic, and low cost, and is suitable for large-scale industrialized production.

[0071] In one embodiment, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and the amino polyol compound is (0.6-1.0):(1.2-2.0):(1.8-3.0), and is 0.6:1.2:1.8, 0.6:1.2:1.9, 0.6:1.2:2.0, 0.6:1.2:2.1, 0.6:1.2:2.2, 0.6:1.2:2.3, 0.6:1.2:2.4, 0.6:1.2:2.5, 0.6:1.2:2.6, 0.6:1.2:2.7, 0.6:1.2:2.8, 0.6:1.2:2.9, 0.6:1.2 :3.0, 0.6:1.5:1.8, 0.6:1.5:1.9, 0.6:1.5:2.0, 0.6:1.5:2.1, 0.6:1.5:2.2, 0.6:1.5:2.3, 0.6:1.5:2.4, 0.6:1.5:2.5, 0.6:1.5:2.6, 0.6:1.5:2.7, 0.6:1.5:2.8, 0.6:1.5:2.9, 0.6:1.5:3.0, 0.6:1.8:1.8, 0.6:1.8:1.9, 0.6:1.8:2.0, 0.6:1.8:2.1, 0.6:1.8:2.2, 0.6:1.8:2.3, 0.6:1.8:2.4, 0.6:1 .8:2.5, 0.6:1.8:2.6, 0.6:1.8:2.7, 0.6:1.8:2.8, 0.6:1.8:2.9, 0.6:1.8:3.0, 0.6:2.0:1.8, 0.6:2.0:1.9, 0.6:2.0:2.0, 0.6:2.0:2.1, 0.6:2.0:2. 2, 0.6:2.0:2.3, 0.6:2.0:2.4, 0.6:2.0:2.5, 0.6:2.0:2.6, 0.6:2.0:2.7, 0.6:2.0:2.8, 0.6:2.0:2.9, 0.6:2.0:3.0, 0.8:1.2:1.8, 0.8:1.2:1.9, 0.8 :1.2:2.0, 0.8:1.2:2.1, 0.8:1.2:2.2, 0.8:1.2:2.3, 0.8:1.2:2.4, 0.8:1.2:2.5, 0.8:1.2:2.6, 0.8:1.2:2.7, 0.8:1.2:2.8, 0.8:1.2:2.9, 0.8:1.2: 3.0, 0.8:1.5:1.8, 0.8:1.5:1.9, 0.8:1.5:2.0, 0.8:1.5:2.1, 0.8:1.5:2.2, 0.8:1.5:2.3, 0.8:1.5:2.4, 0.8:1.5:2.5, 0.8:1.5:2.6, 0.8:1.5:2.7, 0.8:1.5:2.8, 0.8:1.5:2.9, 0.8:1.5:3.0, 0.8:1.8:1.8, 0.8:1.8:1.9, 0.8:1.8:2.0, 0.8:1.8:2.1, 0.8:1.8:2.2, 0.8:1.8:2.3, 0.8:1.8:2.4, 0.8:1.8:2.5, 0.8:1.8:2.6, 0.8:1.8:2.7, 0.8:1.8:2.8, 0.8:1.8:2.9, 0.8:1.8:3.0, 0.8:2.0:1.8, 0.8:2 .0:1.9, 0.8:2.0:2.0, 0.8:2.0:2.1, 0.8:2.0:2.2, 0.8:2.0:2.3, 0.8:2.0:2.4, 0.8:2.0:2.5, 0.8:2.0:2.6, 0.8:2.0:2.7, 0.8:2.0:2.8, 0.8:2.0:2.9, 0.8:2.0:3.0, 1.0:1.5:1.8, 1.0:1.5:1.9, 1.0:1.5:20, 1.0:1.5:2.1, 1.0:1.5:22, 1.0:1.5:2 .3, 1.0:1.5:2.4, 1.0:1.5:2.5, 1.0:1.5:2.6, 1.0:1.5:2.7, 1.0:1.5:2.8, 1.0:1.5:2.9, 1.0:1.5:3.0, 1.0:1.8:1.8, 1.0:1.8:1.9, 1.0:1.8:2.0, 1.0:1.8:2.1, 1.0:1.8:2.2, 1.0:1.8:2.3, 1.0:1.8:2.4, 10:1.8:2.5, 10:1.8:26, 10:1.8:2.7, 1.0:1.8:2. These include, but are not limited to: 0:1.8:2.8, 1.0:1.8:2.9, 1.0:1.8:3.0, 1.0:2.0:1.8, 1.0:2.0:1.9, 1.0:2.0:2.0, 1.0:2.0:2.1, 1.0:2.0:2.2, 1.0:2.0:2.3, 1.0:2.0:2.4, 1.0:2.0:2.5, 1.0:2.0:2.6, 1.0:2.0:2.7, 1.0:2.0:2.8, 1.0:2.0:2.9 and 1.0:2.0:3.0.

[0072] In one embodiment, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and the amino polyol compound is (0.8-1.0):(1.5-2.0):(2.0-3.0).

[0073] In one embodiment, the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and aminopolyol compound is 1.0:2.0:3.0.

[0074] In one embodiment, the amino polyol compound is 3-amino-1,2-propanediol.

[0075] The present application further provides a copper plating solution comprising the above copper plating additive composition.

[0076] In one embodiment, the copper plating solution further comprises water, copper sulfate (CuSO4), sulfuric acid, and chloride ions.

[0077] In one embodiment, the copper plating solution further comprises a brightener, a surfactant, and a leveling agent.

[0078] When the above copper plating additive composition is added to the copper plating solution, a small amount can significantly improve the thickness, brightness and whiteness of the plating layer, without changing the stability of the original copper plating solution and the performance of the original copper plating layer.

[0079] The present application further provides a copper brush plating method for providing a coating layer on the surface of a plastic film, which has a fast plating speed, can obtain a copper film or layer with fine crystals, is continuous and uniform, does not have any adverse effect on the copper plated film or layer, has good bonding strength of the film or layer after plating, and the plated film or layer formed by one brush plating can have a sheet resistance that meets the requirements of the finished product, and does not pierce the plastic film.

[0080] The present application further provides a method for copper plating a surface of a substrate, comprising contacting the substrate with a copper plating solution to effect copper plating.

[0081] The present application further provides a copper brush plating method for providing a coating layer on a surface of a substrate, the method comprising: performing a copper plating process on a surface of a substrate using a copper brush plating method to form a copper film on the surface of the substrate, an anode during the copper plating process being a brush plating roller, and the copper plating process further comprising contacting the surface of the substrate with a copper plating solution.

[0082] The copper brush plating method may further include performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film, thereby forming a substrate.

[0083] In one embodiment, the substrate is made of plastic. Further, the substrate is a plastic film.

[0084] In another embodiment, the substrate includes a first copper film on a surface of a plastic film, where the first copper film is formed by a physical vapor deposition process, such as magnetron sputtering or evaporation.

[0085] In the copper plating process, the relative movement speed of the substrate to the brush plating bath is 3m / min to 10m / min.

[0086] In one embodiment, the copper brush plating method of the present invention comprises: performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film, thereby forming a substrate; performing a second copper plating process on the first copper film using a copper brush plating method to form a third copper film on the first copper film; the anode during the second copper plating process is a brush plating roller; The second copper plating process further comprises contacting the first copper film on the substrate with a copper plating solution that includes a copper plating additive composition.

[0087] Here, the copper plating additive composition comprises 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide and an aminopolyol compound.

[0088] In one embodiment, a copper brush plating method includes: performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film and a second copper film on the other surface of the plastic film; performing a second copper plating process on the first copper film and the second copper film using a copper brush plating method to form a third copper film on the first copper film and a fourth copper film on the second copper film; the anode during the second copper plating process is a brush plating roller; the second copper plating process further comprises contacting the first copper film and the second copper film with a copper plating solution containing the copper plating additive composition; The copper plating additive composition includes 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide and an aminopolyol compound.

[0089] Electric brush plating, also known as metal brush plating, quick plating, and brush plating, is an electrochemical method in which a plating brush immersed in a plating solution is used as an anode, and metal ions are discharged on the surface of the negative electrode (workpiece) to crystallize and form a metal coating layer. The present application creatively changes the brush plating brush to an anode brush plating roller, which can significantly improve the plating speed, production efficiency, fineness of crystal grains, uniformity and continuity of the plating layer, and reduce the risk of perforation in the plastic film. In addition, by using a copper plating solution containing 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and an aminopolyol compound in combination, it can refine the crystal grains, improve the flatness and uniformity of the copper plating layer, increase the thickness of the copper plating layer, and also improve the whiteness, brightness, and color tone of the copper plating layer. In addition, the copper brush plating method does not have any adverse effects on the copper plating film or layer produced by the conventional physical vapor deposition method, and the bonding strength of each film or layer after plating is good, and the plating film or layer formed by one brush plating can meet the sheet resistance requirements of the finished product. The copper plating solution used in the present invention has the advantages of being environmentally friendly, non-toxic, and low cost, and is suitable for large-scale industrial production.

[0090] In one embodiment, the copper brush plating method includes the following steps S1 and S2, and the flow chart is shown in FIG.

[0091] S1, performing a first copper plating process on a plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film and a second copper film on the other surface of the plastic film.

[0092] In one embodiment, the plastic film is made of polypropylene (PP), polyethylene terephthalate (PET), polyethylene (PE), polyacrylonitrile (PAN), polyimide (PI) or polydimethylsiloxane (PDMS).

[0093] In one embodiment, the plastic film has a thickness of 3.2 μm to 12 μm.

[0094] In one embodiment, the physical vapor deposition method is magnetron sputtering or evaporation.

[0095] In one embodiment, the first copper film and the second copper film are both formed by magnetron sputtering.

[0096] In one embodiment, the first copper film and the second copper film are both formed by evaporation.

[0097] In one embodiment, the magnetron sputtering includes the steps of magnetron sputtering nichrome, magnetron sputtering copper.

[0098] In one embodiment, the deposition includes the steps of magnetron sputtering nichrome, magnetron sputtering copper, and evaporating copper.

[0099] In one embodiment, the first copper film has a sheet resistance of less than 2200 mΩ.

[0100] In one embodiment, the sheet resistance of the first copper film is between 100mΩ and 2200mΩ, including but not limited to 100mΩ, 200mΩ, 300mΩ, 400mΩ, 500mΩ, 600mΩ, 700mΩ, 800mΩ, 900mΩ, 1000mΩ, 1100mΩ, 1200mΩ, 1300mΩ, 1400mΩ, 1500mΩ, 1600mΩ, 1700mΩ, 1800mΩ, 1900mΩ, 2000mΩ, 2100mΩ, or 2200mΩ.

[0101] In one embodiment, the first copper film has a sheet resistance of less than 1500 mΩ.

[0102] In one embodiment, the first copper film has a sheet resistance of less than 500 mΩ.

[0103] In one embodiment, the thickness of the first copper film is between 0.1 μm and 0.5 μm, including but not limited to 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, and 0.5 μm.

[0104] In one embodiment, the sheet resistance of the second copper film is less than 2200 mΩ.

[0105] In one embodiment, the sheet resistance of the second copper film is between 100mΩ and 2200mΩ, including but not limited to 100mΩ, 200mΩ, 300mΩ, 400mΩ, 500mΩ, 600mΩ, 700mΩ, 800mΩ, 900mΩ, 1000mΩ, 1100mΩ, 1200mΩ, 1300mΩ, 1400mΩ, 1500mΩ, 1600mΩ, 1700mΩ, 1800mΩ, 1900mΩ, 2000mΩ, 2100mΩ, or 2200mΩ.

[0106] In one embodiment, the sheet resistance of the second copper film is less than 1500 mΩ.

[0107] In one embodiment, the sheet resistance of the second copper film is less than 500 mΩ.

[0108] In one embodiment, the thickness of the second copper film is between 0.1 μm and 0.5 μm, including but not limited to 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, and 0.5 μm.

[0109] S2: A second copper plating process is performed on the first copper film and the second copper film using a copper brush plating method to form a third copper film on the first copper film and a fourth copper film on the second copper film.

[0110] In this application, the anode during the second copper plating process is a brush plating roller. By changing the brush plating brush to an anode brush plating roller, the plating speed, production efficiency, fineness of crystal grains, uniformity and continuity of the plating layer can be significantly improved, and the risk of perforation of the plastic film can be reduced.

[0111] In one embodiment, the brush plating roller is covered with a sponge-like liquid-absorbing layer, which can eliminate the problem of the brush plating roller being copper-plated and avoid the copper film being pierced by the copper plating of the brush plating roller.

[0112] In one embodiment, the brush plating apparatus of the present application includes an unwinding system, a brush plating system, a rinsing system, a baking system, and a winding system.

[0113] In one embodiment, the schematic diagram of the brush plating equipment of the present application can be seen in FIG. 2, and includes an unwinding system 1, a brush plating bath 2, a water-blocking roller 3, a cathode conductive roller 4, an anode brush plating roller 5, a clip oven 6, and a winding system 7. A plurality of water-blocking rollers 3 may be arranged in the equipment. Three to six anode brush plating rollers 5 may be provided in between, and the anode brush plating roller 5 may be covered with a sponge-like liquid-absorbing layer. In addition, the brush plating system and the baking system may include an oxidation prevention system that performs an oxidation prevention treatment on the copper plating layer to improve the oxidation prevention ability and extend the service life.

[0114] In this application, the copper plating solution used in the second copper plating process includes water, copper sulfate, sulfuric acid, chloride ions, 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide and aminopolyol compound. Copper sulfate provides the basis for copper plating, and forms an adsorption layer with sulfuric acid, slowing down the substitution rate, inhibiting side reactions, reducing the porosity of the copper layer during the substitution reaction, and improving the binding force. Chloride ions provide the basis for the formation of a shiny copper plating layer, and also react with monovalent copper ions to produce CuCl precipitates, reducing the production of "copper powder" in the plating layer, making the crystals of the plating layer dense, fine and not coarse. 1,4-Cyclohexanedione monoethylene acetal can significantly improve the brightness of the copper brush plating layer; potassium phthalimide can effectively improve the dissolution efficiency of 1,4-cyclohexanedione monoethylene acetal, and also play the role of refining the crystal grains, leveling, improving the uniformity of the plating layer, and increasing the thickness of the plating layer; aminopolyol compound can greatly change the color tone of the copper layer, making it more vivid.

[0115] In one embodiment, the second copper plating process is performed under the following parameters: plating temperature 0° C. to 45° C., plating time 1 min to 10 min, operating voltage 1 to 7 V, and relative movement speed of the plastic film to the brush plating roller 3 m / min to 10 m / min.

[0116] Plating temperatures include, but are not limited to, 0°C, 2°C, 5°C, 8°C, 10°C, 12°C, 15°C, 18°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, and 45°C. Plating times include, but are not limited to, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.5 min, and 10 min. The operating voltage includes, but is not limited to, 1V, 2V, 3V, 4V, 5V, 6V and 7V. It can be understood that the relative movement speed of the plastic film to the brush plating roller is 3m / min, 3.5m / min, 4m / min, 4.5m / min, 5m / min, 5.5m / min, 6m / min, 6.5m / min, 7m / min, 7.5m / min, 8m / min, 8.5m / min, 9m / min, 9.5m / min and 10m / min.

[0117] The present application will now be further described with reference to specific examples. EXAMPLES

[0118] (1) In this embodiment, 1,4-Cyclohexanedione monoethylene acetal 10g, 20 g potassium phthalimide, and One liter of an aqueous solution of the copper plating additive composition containing 30 grams of 3-amino-1,2-propanediol was prepared. (2) In this embodiment, water, 1,4-Cyclohexanedione monoethylene acetal 0.10g, Potassium phthalimide 0.20g, 0.30g 3-amino-1,2-propanediol, Copper sulfate 120g, 70g sulfuric acid, Chloride ion 70mg, Ethylenethiourea 0.0005mg, Sodium dodecyl sulfonate 0.08 mg, and One liter of the copper plating solution containing 0.07 g of polyethylene glycol was prepared.

[0119] (3) The copper plating solution of this example was prepared by a method including the following steps:

[0120] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 10 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0121] 2) Preparation of potassium phthalimide: 20 g of potassium phthalimide was weighed out on an analytical balance.

[0122] 3) Preparation of 3-amino-1,2-propanediol solution: 30 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0123] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0124] 5) Copper sulfate, sulfuric acid, hydrogen chloride, ethylenethiourea, sodium dodecylsulfonate and polyethylene glycol were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0125] (4) Copper brush plating was performed to provide a coating layer on the surface of the PP film, and the method included the following steps:

[0126] The PP film was subjected to copper brush plating for 5 minutes under the following conditions: plating temperature of the plating solution was 40℃, relative movement speed of the plastic film against the brush plating roller was 7m / min, and operating voltage of the brush plating was 2V. Then, the plating layer was slowly washed with flowing deionized water and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0127] (5) As a comparative example, a PP film was subjected to copper brush plating treatment using a copper plating solution not containing the copper plating additive composition under the same conditions as (4), and the plating layer was washed and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0128] (6) Detection results 3, the copper plating layer (a) formed on the workpiece by brush plating with the additive composition is 3.52 μm thick, has a smooth surface and a glossy copper color, whereas the copper plating layer formed on the workpiece by brush plating without the additive composition is 1.06 μm thick, has a rough surface and a dull reddish brown color. EXAMPLES

[0129] (1) In this embodiment, 1,4-Cyclohexanedione monoethylene acetal 6g, Potassium phthalimide, 12 g; and One liter of an aqueous solution of the copper plating additive composition containing 18 grams of 3-amino-1,2-propanediol was prepared.

[0130] (2) In this embodiment, water, 1,4-Cyclohexanedione monoethylene acetal 0.06g, Potassium phthalimide 0.12g, 3-amino-1,2-propanediol 0.18g, Copper sulfate 150g, 60g of sulfuric acid, Chloride ion 70mg, Ethylenethiourea 0.0005mg, Sodium dodecyl sulfonate 0.08 mg, and One liter of the copper plating solution containing 0.07 g of polyethylene glycol was prepared.

[0131] (3) The copper plating solution of this example was prepared by a method including the following steps:

[0132] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 6 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0133] 2) Preparation of potassium phthalimide: 12 g of potassium phthalimide was weighed out using an analytical balance.

[0134] 3) Preparation of 3-amino-1,2-propanediol solution: 18 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0135] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0136] 5) Copper sulfate, sulfuric acid, hydrogen chloride, ethylenethiourea, sodium dodecylsulfonate and polyethylene glycol were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0137] (4) Copper brush plating was performed to provide a coating layer on the surface of the PP film, and the method included the following steps:

[0138] The PP film was subjected to copper brush plating for 5 minutes under the following conditions: plating temperature of the plating solution was 40℃, relative movement speed of the plastic film against the brush plating roller was 7m / min, and operating voltage of the brush plating was 2V. Then, the plating layer was slowly washed with flowing deionized water and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0139] (5) As a comparative example, a PP film was subjected to copper brush plating treatment using a copper plating solution not containing the copper plating additive composition under the same conditions as (4), and the plating layer was washed and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0140] (6) Detection results 3, the copper plating layer (b) formed on the workpiece by brush plating with the additive composition is 3.14 μm thick, has a smooth surface and a glossy copper color, whereas the copper plating layer formed on the workpiece by brush plating without the additive composition is 0.98 μm thick, has a rough surface and a dull reddish brown color. EXAMPLES

[0141] (1) In this embodiment, 1,4-Cyclohexanedione monoethylene acetal 7g, Potassium phthalimide, 14 g; and One liter of an aqueous solution of the copper plating additive composition containing 21 g of 3-amino-1,2-propanediol was prepared.

[0142] (2) In this embodiment, water, 1,4-Cyclohexanedione monoethylene acetal 0.07g, Potassium phthalimide 0.14g, 3-amino-1,2-propanediol 0.21g, Copper sulfate 180g, Sulfuric acid 50g, Chloride ion 60mg, Ethylenethiourea 0.0002mg, Sodium dodecyl sulfonate 0.05 mg, and One liter of the copper plating solution containing 0.05 g of polyethylene glycol was prepared.

[0143] (3) The copper plating solution of this example was prepared by a method including the following steps:

[0144] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 7 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0145] 2) Preparation of potassium phthalimide: 14 g of potassium phthalimide was weighed out using an analytical balance.

[0146] 3) Preparation of 3-amino-1,2-propanediol solution: 21 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0147] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0148] 5) Copper sulfate, sulfuric acid, hydrogen chloride, ethylenethiourea, sodium dodecylsulfonate and polyethylene glycol were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0149] (4) Copper brush plating was performed to provide a coating layer on the surface of the PP film, and the method included the following steps:

[0150] The PP film was subjected to copper brush plating for 5 minutes under the following conditions: plating temperature of the plating solution was 40℃, relative movement speed of the plastic film against the brush plating roller was 7m / min, and operating voltage of the brush plating was 2V. Then, the plating layer was slowly washed with flowing deionized water and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0151] (5) As a comparative example, a PP film was subjected to copper brush plating treatment using a copper plating solution not containing the copper plating additive composition under the same conditions as (4), and the plating layer was washed and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0152] (6) Detection results 3, the copper plating layer (c) formed on the workpiece by brush plating with the additive composition is 3.21 μm thick, has a smooth surface and a glossy copper color, whereas the copper plating layer formed on the workpiece by brush plating without the additive composition is 1.05 μm thick, has a rough surface and a dull reddish brown color. EXAMPLES

[0153] (1) In this embodiment, 1,4-Cyclohexanedione monoethylene acetal 8g, Potassium phthalimide, 16 g, and One liter of an aqueous solution of the copper plating additive composition containing 24 grams of 3-amino-1,2-propanediol was prepared.

[0154] (2) In this embodiment, water, 1,4-Cyclohexanedione monoethylene acetal 0.08g, Potassium phthalimide 0.16g, 3-amino-1,2-propanediol 0.24g, Copper sulfate 200g, 70g sulfuric acid, Chloride ion 80mg, Ethylenethiourea 0.0008mg, Sodium dodecyl sulfonate 0.1 mg, and One liter of the copper plating solution containing 0.05 g of polyethylene glycol was prepared.

[0155] (3) The copper plating solution of this example was prepared by a method including the following steps:

[0156] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 8 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0157] 2) Preparation of potassium phthalimide: 16 g of potassium phthalimide was weighed out on an analytical balance.

[0158] 3) Preparation of 3-amino-1,2-propanediol solution: 24 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0159] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0160] 5) Copper sulfate, sulfuric acid, hydrogen chloride, ethylenethiourea, sodium dodecylsulfonate and polyethylene glycol were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0161] (4) Copper brush plating was performed to provide a coating layer on the surface of the PP film, and the method included the following steps:

[0162] The PP film was subjected to copper brush plating for 5 minutes under the following conditions: plating temperature of the plating solution was 40℃, relative movement speed of the plastic film against the brush plating roller was 7m / min, and operating voltage of the brush plating was 2V. Then, the plating layer was slowly washed with flowing deionized water and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0163] (5) As a comparative example, a PP film was subjected to copper brush plating treatment using a copper plating solution not containing the copper plating additive composition under the same conditions as (4), and the plating layer was washed and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0164] (6) Detection results In this example, the copper plating layer formed on the workpiece by brush plating with the additive composition was 3.31 μm thick, had a smooth surface and a glossy copper color, whereas the copper plating layer formed on the workpiece by brush plating without the additive composition was 1.02 μm thick, had a rough surface and a dull reddish brown color. EXAMPLES

[0165] (1) In this embodiment, 1,4-Cyclohexanedione monoethylene acetal 9g, Potassium phthalimide, 18 g; and One liter of an aqueous solution of the copper plating additive composition containing 27 grams of 3-amino-1,2-propanediol was prepared.

[0166] (2) In this embodiment, water, 1,4-Cyclohexanedione monoethylene acetal 0.09g, Potassium phthalimide 0.18g, 3-amino-1,2-propanediol 0.27g, Copper sulfate 220g, 70g sulfuric acid, Chloride ion 60mg, Ethylenethiourea 0.0008mg, Sodium dodecyl sulfonate 0.1 mg, and One liter of the copper plating solution containing 0.06 g of polyethylene glycol was prepared.

[0167] (3) The copper plating solution of this example was prepared by a method including the following steps:

[0168] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 9 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0169] 2) Preparation of potassium phthalimide: 18 g of potassium phthalimide was weighed out on an analytical balance.

[0170] 3) Preparation of 3-amino-1,2-propanediol solution: 27 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0171] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0172] 5) Copper sulfate, sulfuric acid, hydrogen chloride, ethylenethiourea, sodium dodecylsulfonate and polyethylene glycol were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0173] (4) Copper brush plating was performed to provide a coating layer on the surface of the PP film, and the method included the following steps:

[0174] The PP film was subjected to copper brush plating for 5 minutes under the following conditions: plating temperature of the plating solution was 40℃, relative movement speed of the plastic film against the brush plating roller was 7m / min, and operating voltage of the brush plating was 2V. Then, the plating layer was slowly washed with flowing deionized water and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0175] (5) As a comparative example, a PP film was subjected to copper brush plating treatment using a copper plating solution not containing the copper plating additive composition under the same conditions as (4), and the plating layer was washed and dried. The thickness of the copper plating layer was measured using the Fischei measurement method, and the appearance of the copper plating layer was observed.

[0176] (6) Detection results In this example, the copper plating layer formed on the workpiece by brush plating with the additive composition was 3.36 μm thick, had a smooth surface and a glossy copper color, whereas the copper plating layer formed on the workpiece by brush plating without the additive composition was 1.34 μm thick, had a rough surface and a dull reddish brown color.

[0177] According to the above examples, the present application has technical effects such as improving the bonding strength of the plating layer, refining the crystal grains, and avoiding perforation of the plating layer without adversely affecting the original performance of the high-speed copper brush plating solution, and can obtain a continuous, uniform copper plating layer with fine crystals, which can fully meet the needs of large-scale industrial production. EXAMPLES

[0178] This example provides a copper plating method for a PP film, which includes the following steps:

[0179] (1) A copper plating solution was prepared. In this example, the solution contained water, 1,4-Cyclohexanedione monoethylene acetal 0.1g, Potassium phthalimide 0.2g, 0.3g 3-amino-1,2-propanediol, Copper sulfate 220g, 60 g sulfuric acid, and One liter of the copper plating solution containing 70 mg of chloride ions was prepared.

[0180] The copper plating solution of this example was prepared by a method including the following steps.

[0181] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 10 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0182] 2) Preparation of potassium phthalimide: 20 g of potassium phthalimide was weighed out on an analytical balance.

[0183] 3) Preparation of 3-amino-1,2-propanediol solution: 30 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0184] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0185] 5) Copper sulfate, sulfuric acid and hydrogen chloride were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0186] (2) First, magnetron sputtering of nichrome was performed on the PP film, followed by magnetron sputtering of copper (first copper plating process), and the resulting copper film was tested. (1) The sheet resistance of the copper film was tested by sampling at two points on the film, the first test result was 131mΩ, and the second test result was 207mΩ. (2) Tape was applied to the copper film and peeled off by hand, resulting in sporadic copper chips peeling off from the tail of the film. (3) By illuminating the back of the film with a mobile phone, it was observed that the copper film had micropores. (4) The thickness of the copper film measured by the Fischei measurement method was 0.237μm.

[0187] (3) A second copper plating process was performed on the copper film using copper brush plating.

[0188] The brush plating equipment shown in Figure 2 was used to perform a second copper plating process on the copper film with the following parameters: plating temperature 30°C, plating time 1 min, operating voltage 1 V, and relative movement speed of the plastic film to the brush plating roller 5 m / min. The copper film was tested. (1) The sheet resistance of the copper film was tested by sampling at two points on the film, and the test result of the first point was 3.6 mΩ, and the test result of the second point was 3.26 mΩ. (2) Tape was attached to the copper film and peeled off by hand, and the copper was not peeled off. Therefore, the copper film passed the adhesion test. (3) The film after copper brush plating was shiny, and no other holes were observed except for the holes formed in the sheet resistance test. (4) The thickness of the copper film measured by the Fischei measurement method was 1.995 μm, and the film thickness increased by brush plating was 1.758 μm. EXAMPLES

[0189] This example provides a copper plating method for a PP film, which includes the following steps:

[0190] (1) A copper plating solution was prepared. In this example, the solution contained water, 1,4-Cyclohexanedione monoethylene acetal 0.6g, Potassium phthalimide 0.12g, 3-amino-1,2-propanediol 0.18g, Copper sulfate 220g, 60 g sulfuric acid, and One liter of the copper plating solution containing 70 mg of chloride ions was prepared.

[0191] The copper plating solution of this example was prepared by a method including the following steps.

[0192] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 10 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0193] 2) Preparation of potassium phthalimide: 20 g of potassium phthalimide was weighed out on an analytical balance.

[0194] 3) Preparation of 3-amino-1,2-propanediol solution: 30 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0195] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0196] 5) Copper sulfate, sulfuric acid and hydrogen chloride were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0197] (2) First, magnetron sputtering of nichrome was performed on the PP film, followed by magnetron sputtering of copper (first copper plating process), and the resulting copper film was tested. (1) The sheet resistance of the copper film was tested, and the test result was 388mΩ. (2) Tape was applied to the copper film and peeled off by hand, and the adhesion passed the test. (3) By illuminating the back of the film with a mobile phone, it was observed that the copper film had micropores. (4) The thickness of the copper film measured by the Fischei measurement method was 0.357μm.

[0198] (3) A second copper plating process was performed on the copper film using copper brush plating.

[0199] Using the brush plating equipment shown in Figure 2, a second copper plating process was performed on the copper film with the following parameters: plating temperature 30°C, plating time 2 min, operating voltage 1 V, and relative movement speed of the plastic film to the brush plating roller 5 m / min. The created copper film was tested. (1) The sheet resistance of the copper film was tested, and the test result was 7.66 mΩ. (2) Tape was applied to the copper film and peeled off by hand, and the copper was not peeled off. Therefore, the copper film passed the adhesion test. (3) The film after copper brush plating was shiny, and no other holes were observed other than the holes formed in the sheet resistance test. (4) The thickness of the copper film measured by the Fischei measurement method was 0.913 μm, and the film thickness increased by brush plating was 0.556 μm. EXAMPLES

[0200] This example provides a copper plating method for a PP film, which includes the following steps:

[0201] (1) A copper plating solution was prepared. In this example, the solution contained water, 1,4-Cyclohexanedione monoethylene acetal 0.7g, Potassium phthalimide 0.14g, 3-amino-1,2-propanediol 0.21g, Copper sulfate 220g, 60 g sulfuric acid, and One liter of the copper plating solution containing 70 mg of chloride ions was prepared.

[0202] The copper plating solution of this example was prepared by a method including the following steps.

[0203] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 10 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0204] 2) Preparation of potassium phthalimide: 20 g of potassium phthalimide was weighed out on an analytical balance.

[0205] 3) Preparation of 3-amino-1,2-propanediol solution: 30 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0206] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0207] 5) Copper sulfate, sulfuric acid and hydrogen chloride were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0208] (2) First, magnetron sputtering of nichrome was performed on the PP film, followed by magnetron sputtering of copper (first copper plating process), and the resulting copper film was tested. (1) The sheet resistance of the copper film was tested, and the test result was 121mΩ. (2) Tape was applied to the copper film and peeled off by hand, and the adhesion passed. (3) By illuminating the back of the film with a mobile phone, it was observed that the copper film had micropores. (4) The thickness of the copper film measured by the Fischei measurement method was 0.371μm.

[0209] (3) A second copper plating process was performed on the copper film using copper brush plating.

[0210] Using the brush plating equipment shown in Figure 2, a second copper plating process was performed on the copper film with the following parameters: plating temperature 30°C, plating time 3 min, operating voltage 1 V, and relative movement speed of the plastic film to the brush plating roller 5 m / min. The created copper film was tested. (1) The sheet resistance of the copper film was tested, and the test result was 5.21 mΩ. (2) Tape was applied to the copper film and peeled off by hand, and the copper was not peeled off. Therefore, the adhesion test was passed. (3) The film surface after copper brush plating was shiny, and no other holes were observed except for the holes formed in the sheet resistance test. (4) The thickness of the copper film measured by the Fischei measurement method was 0.875 μm, and the film thickness increased by brush plating was 0.504 μm. EXAMPLES

[0211] This example provides a method for copper plating a PET film, which includes the following steps:

[0212] (1) A copper plating solution was prepared. In this example, the solution contained water, 1,4-Cyclohexanedione monoethylene acetal 0.06g, Potassium phthalimide 0.12g, 0.25g 3-amino-1,2-propanediol, Copper sulfate 200g, 60g of sulfuric acid, Chloride ion 70mg, Ethylenethiourea 0.0002mg, Sodium dodecyl sulfonate 0.05 mg, and One liter of the copper plating solution containing 0.05 g of polyethyleneimine alkyl salt was prepared.

[0213] The copper plating solution of this example was prepared by a method including the following steps.

[0214] 1) Preparation of 1,4-cyclohexanedione monoethylene acetal solution: 6 g of 1,4-cyclohexanedione monoethylene acetal was dissolved in 200 ml of deionized water and stirred until clear.

[0215] 2) Preparation of potassium phthalimide: 12 g of potassium phthalimide was weighed out using an analytical balance.

[0216] 3) Preparation of 3-amino-1,2-propanediol solution: 25 g of 3-amino-1,2-propanediol was dissolved in 500 ml of deionized water and stirred until clear.

[0217] 4) Preparation of copper plating additive composition: The potassium phthalimide weighed in step 2) was slowly added to the 1,4-cyclohexanedione monoethylene acetal solution prepared in step 1), and stirred thoroughly to dissolve and mix uniformly. The solution was then slowly added to the 3-amino-1,2-propanediol solution prepared in step 3), followed by adding deionized water until the total volume reached 1 L, and stirring was continued to mix each component uniformly.

[0218] 5) Copper sulfate, sulfuric acid, hydrogen chloride, ethylenethiourea, sodium dodecylsulfonate and polyethyleneimine alkyl salt were mixed in water, and then 10 ml of the copper plating additive composition prepared in step 4) was added thereto.

[0219] (2) First, magnetron sputtering of nichrome was performed on the PET film, followed by magnetron sputtering of copper (first copper plating process), and the resulting copper film was tested. (1) The sheet resistance of the copper film was tested, and the test result was 400mΩ. (2) Tape was applied to the copper film and peeled off by hand, and the adhesion passed. (3) By illuminating the back of the film with a mobile phone, it was observed that the copper film had micropores. (4) The thickness of the copper film measured by the Fischei measurement method was 0.34μm.

[0220] (3) A second copper plating process was performed on the first copper film and the second copper film using a copper brush plating method.

[0221] Using the brush plating equipment shown in Figure 2, a second copper plating process was performed on the copper film with the following parameters: plating temperature 30°C, plating time 3 min, operating voltage 5 V, and relative movement speed of the plastic film to the brush plating roller 7 m / min. The copper film was tested. (1) The sheet resistance of the copper film was tested, and the test result was 5.12 mΩ. (2) Tape was applied to the copper film and peeled off by hand, and the copper was not peeled off. Therefore, the adhesion test was passed. (3) The film surface after brush plating was shiny, and no other holes were observed except for the holes formed in the sheet resistance test. (4) The thickness of the copper film measured by the Fischei measurement method was 0.885 μm, and the film thickness increased by brush plating was 0.545 μm.

[0222] Each technical feature of the above embodiments can be combined in any manner, and for the sake of brevity, not all possible combinations of each technical feature in the above embodiments are described, but combinations of these technical features should be considered to be within the scope described in this specification, unless there is a contradiction.

[0223] The above examples merely show some embodiments of the present application, and the description is specific and detailed, but it should not be understood as limiting the scope of the invention. In addition, those skilled in the art can make various modifications and improvements without departing from the concept of the present application, and all of these are within the scope of protection of the present application. Therefore, the scope of protection of the patent of the present application should be in accordance with the scope of the attached claims.

Claims

1. A copper plating additive composition comprising 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide and an aminopolyol compound.

2. The copper plating additive composition according to claim 1, characterized in that the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and amino polyol compound is (0.6-1.0):(1.2-2.0):(1.8-3.0).

3. The copper plating additive composition according to claim 1 or 2, characterized in that the mass ratio of 1,4-cyclohexanedione monoethylene acetal, potassium phthalimide, and aminopolyol compound is (0.8-1.0):(1.5-2.0):(2.0-3.0).

4. 4. The copper plating additive composition according to claim 1, wherein the amino polyol compound is 3-amino-1,2-propanediol.

5. A copper plating solution comprising the copper plating additive composition according to any one of claims 1 to 4.

6. 6. The copper plating solution according to claim 5, further comprising water, copper sulfate, sulfuric acid, and chloride ions.

7. The copper plating solution per liter contains water, 1,4-cyclohexanedione monoethylene acetal 0.06 g to 0.10 g, Potassium phthalimide 0.12g to 0.20g, Aminopolyol compound 0.18 g to 0.30 g, Copper sulfate 120g to 220g, 50g to 70g sulfuric acid, and Contains 60mg to 80mg of chloride ion.

7. The copper plating solution according to claim 5 or 6.

8. 8. The copper plating solution according to claim 5, further comprising a brightener, a surfactant and a leveling agent.

9. 9. The copper plating solution according to claim 8, wherein the brightener is one or more selected from the group consisting of ethylenethiourea, benzimidazole, and aliphatic amine ethoxysulfonate.

10. 10. The copper plating solution according to claim 8, wherein the surfactant is one or two selected from the group consisting of sodium dodecylsulfonate and 3,3'-dithiobis(sodium 1-propanesulfonate).

11. 11. The copper plating solution according to claim 8, wherein the leveling agent is one or more selected from the group consisting of polyethylene glycol, 1,4-butynediol, and polyethyleneimine alkyl salts.

12. The copper plating solution per liter contains water, 1,4-cyclohexanedione monoethylene acetal 0.06 g to 0.10 g, Potassium phthalimide 0.12g to 0.20g, Aminopolyol compound 0.18 g to 0.30 g, Copper sulfate 120g to 220g, Sulfuric acid 50g to 70g, Chloride ion 60mg to 80mg, Brightener 0.0002mg to 0.0008mg, 0.05 mg to 0.1 mg of a surfactant, and Leveling agent 0.05g to 0.1g, The copper plating solution according to any one of claims 8 to 11.

13. The copper plating solution per liter contains water, 1,4-cyclohexanedione monoethylene acetal 0.06 g to 0.10 g, Potassium phthalimide 0.12g to 0.20g, Aminopolyol compound 0.18 g to 0.30 g, Copper sulfate 120g to 220g, Sulfuric acid 50g to 70g, Chloride ion 60mg to 80mg, Ethylenethiourea 0.0002mg to 0.0008mg, Sodium dodecyl sulfonate 0.05 mg to 0.1 mg, and Polyethylene glycol 0.05g to 0.1g The copper plating solution according to any one of claims 8 to 12.

14. 14. A method for copper plating a surface of a substrate, comprising the step of contacting the substrate with the copper plating solution according to claim 5 to perform a copper plating treatment.

15. Plating temperature: 35℃ to 45℃ Plating time: 1 to 2 minutes. The method for copper plating of a surface of a substrate according to claim 14, characterized in that it is carried out at one or more parameters selected from: an operating voltage of 2V to 7V.

16. performing a copper plating process on a surface of the substrate using a copper brush plating method to form a copper film on the surface of the substrate; The anode during the copper plating process is a brush plating roller; 14. A copper brush plating method for providing a coating layer on a surface of a substrate, wherein the copper plating process further comprises contacting the surface of the substrate with the copper plating solution according to any one of claims 5 to 13.

17. 17. The copper brush plating method of claim 16, further comprising the step of performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film, thereby forming a substrate.

18. performing a first copper plating process on the plastic film using physical vapor deposition to form a first copper film on one surface of the plastic film and a second copper film on the other surface of the plastic film; performing a second copper plating process on the first copper film and the second copper film using a copper brush plating method to form a third copper film on the first copper film and a fourth copper film on the second copper film; the anode during said second copper plating process is a brush plating roller; 14. A copper brush plating method for providing a coating layer on a surface of a substrate, wherein the second copper plating process further comprises contacting the first copper film and the second copper film with the copper plating solution according to claim 5.

19. 19. The copper brush plating method of claim 18, wherein the sheet resistance of the first copper film and the second copper film is 2200 mΩ or less, and / or the thickness of the first copper film and the second copper film is independently 0.1 μm to 0.5 μm.

20. The second copper plating process is Plating temperature: 0℃ to 45℃ Plating time: 1 to 10 minutes Operating voltage: 1V to 7V, 20. The copper brush plating method according to claim 18 or 19, characterized in that the copper brush plating method is performed with one or more parameters selected from: a relative movement speed of the plastic film with respect to the brush plating roller: 3 m / min to 10 m / min.

21. 21. The copper brush plating method according to claim 17, wherein the plastic film has a thickness of 3.2 μm to 12 μm.

22. 22. The copper brush plating method according to claim 17, wherein the physical vapor deposition is a magnetron sputtering method or an evaporation method.

23. 23. The copper brush plating method according to claim 16, wherein the brush plating roller is covered with a sponge-like liquid absorbing layer.

Citation Information

Patent Citations

  • Manufacturing method of plastic film-based copper foil and copper foil prepared by same

    CN113502474A

  • Viscous plating liquid and plating method thereof

    JP1986276993A

  • Copper electroplating solution

    JP1993230687A

  • Additive for pulse copper-plating bath, and pulse copper-plating bath using the same

    JP2008266722A

  • Electrolytic copper plating bath and electronic part having electrodeposited film formed by the bath

    JP2013053336A